Enhancing investment through cyber security policies – Case of Albania - Vilma TOMCO; Klorenta Janushi PASHAJ (Smart Cities and Regional Development Journal)
Today the security of a nation state is not only restricted to its borders and sovereignty but it also extends to protecting against new borderless risks and threats. Globalization and the growth of an interconnected global environment through the Internet have brought immense societal benefits but have also opened up new venues for attacks and threats from governments, criminals, terrorists, private companies, and individuals. The emergence of actors from different locations, with different motives and the desire to challenge the rule of law and international order who can employ readily available tools and operate in a global cyber environment makes it incredibly challenging for nation states to successfully employ protective measures.In this article will be drawn a clear picture of the current situation of the cyber ecosystem in Republic of Albania. Then will be reviewed the investment of the private and public sector in the field of cyber security. At the end will be given recommandations stated in the Value section below. Prior work In January 2017, was approved the law on Cyber Security and bylaws on Critical and Important Information Infrastructures. Since Albania is non-EU member state, the NIS Directive is not fully transposed in the law, but there is a good will between actors to improve the current cyber security situation. Approach In order to capture the evidences in this article are used the methods of observation and case study of different information systems in Albania. Moreover, in order to analyze benefits of increasing the investment on cyber security, different cases from the region and Europe will be shown. Results As information technology is developing rapidly, it is necessary to apply innovative, simple and secure methods, and increase investments in the cyber security field. In this article will be shown the real statistics of how the sectors have invests after the approval of the legal framework in Albania.. Implications This article contains implications for the groups of academics, who can use the statics and case studies in order to improve and update their lectures; for researchers who can take to another level the recommendations and for the practitioners who can update their knowledge on cyber security field in Albania. Value This article gives recommandations for building a high protected information system or mechanism for raising the level of security of the information systems. It also contains guidelines for public administration and private sector for building resilience in cyber security ecosystem in Albania.